Risk Factors for Maternal Mortality in Banyumas Regency in 2022 - Aryani, Aisyah Apriliciciliana; Nafisah, Lu'lu; Hapsari, Pramesthi Widya; Mulyani, Jajang Dede (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2024)
Abstract Introduction: Maternal mortality Rate (MMR) in Banyumas Regency, Indonesia fluctuates. In 2022, it was the highest in Central Java Province with 24 cases spread across 14 Puskesmas. The purpose of this study was to determine the risk factors affecting maternal mortality consisting of maternal education level, anemia status, nutritional status, and history of infectious diseases.Methods: This type of research was a case control study with a sample size of 24 cases and 48 controls. The sampling method was total sampling. Education level, infectious disease, anemia, and nutritional status were investigated. This study was conducted on July to September 2023 in Banyumas Regency, Central Java, Indonesia. Data were collected through interviews using structured questionnaires. Data were analyzed with chi square tests and logistic regression.Results: The results showed that factors that increase the risk of maternal mortality were having a history of infectious diseases (OR = 5.84; 95% CI = 1.46 - 23.33, p = 0.012) and maternal Chronic Energy Deficiency (OR = 3.98; 95% CI = 1.32 - 12.01, p = 0.014).Conclusion: The risk factors for maternal mortality were infectious diseases and maternal Chronic Energy Deficiency. Early detection of risk factors such as history of infectious disease and Chronic Energy Deficiency are needed so prevention efforts can be planned. The improvement of antenatal and postnatal care through increasing the quality of health workers by providing technical and non-technical skills, especially village midwives is very important.